Ongoing Research at the International Livestock Research Institute (ILRI) - CGIAR Research Program on Climate Change, Agriculture and Food Security (2014)
The International Livestock Research Institute in Nairobi is a busy research hub with activities taking place in every corner. The campus is home to animal research and anything that touches on livestock including fodder growth and storage. Photos: S.Kilungu (CCAFS)